Revision of the oryctocephalid trilobite genera Arthricocephalus Bergeron and Oryctocarella Tomashpolskaya and Karpinski (Cambrian) from South China and Siberia. (7th August 2017) - Peng, Shanchi; Babcock, Loren E.; Zhu, Xuejian; Lei, Qianping; Dai, Tao
Abstract: Restudy of the limestone slab containing the type suite of Arthricocephalus chauveaui Bergeron, 1899 (Trilobita), the type species of Arthricocephalus Bergeron, 1899, shows that specimens of three species, each representing a separate genus, are present on the slab and were likely included in the original concept of the species. Besides A . chauveaui, the slab contains specimens of Oryctocarella duyunensis (Qian, 1961) and Duyunaspis duyunensis Zhang and Qian in Zhou et al., 1977. Bergeron (1899) illustrated one exoskeleton from the type suite of A . chauveaui only and apparently based much of his written description on that specimen. This specimen was clearly intended to be the type specimen of A . chauveaui . Subsequently, Lane et al. (1988) designated another specimen, which was not originally illustrated, as the lectotype, and this specimen is referable to Oryctocarella duyunensis . As revised here, Bergeron's illustrated specimen should be regarded as the lectotype of A . chauveaui . Such designation stabilizes the concepts of both Arthricocephalus and A . chauveaui . Arthricocephalites Qian in Lu et al., 1974 and Haliplanktos Blaker and Peel, 1997 are regarded as junior synonyms of Arthricocephalus . Oryctocarella Tomashpolskaya and Karpinski, 1961, which was previously regarded as a junior synonym of Arthricocephalus, is revived as a valid genus. Oryctocarella includes a number of species previously assigned to Arthricocephalus . The type species of both Arthricocephalus and Oryctocarella, together with related species, are described on the basis of new material.